"I Want a Beautiful Life": Divergent Chronotopes in English language Teacher Education. Issue 4 (2nd October 2017) - Aydarova, Elena
Abstract : Research on second language teacher education (SLTE) has focused on the processes, practices, and contexts of teachers' learning to teach. The interaction between SLTE and the broader sociopolitical processes has received less attention. To address this gap, the author explores how SLTE programs in Russia have become positioned at the intersections of transnational educational reforms, such as the Bologna Process, and global cultural flows of migration. Drawing on a multisited critical ethnography, the author analyzes how faculty members and students appropriate SLTE spaces based on their divergent chronotopes (Bakhtin, 1981) and orientations toward English. Although faculty adhere to an aesthetic orientation of taking trips to the imaginary West, many SLTE students follow an instrumental approach of using SLTE spaces to gain linguistic capital for professional and geographic mobility. These contradictory orientations and divergent chronotopes create frictions within programs. As a result of students' pursuit of a better life elsewhere, SLTE programs fail to fulfill their primary mission of preparing English teachers for schools. The significance of this study lies in expanding the focus of inquiry on SLTE and introducing new lens through which to examine the contradictions that emerge in language learning spaces.